Management of adenomyosis in infertile women: comparison between laparotomic resection and administration of aromatase inhibitor (Experience in 55 cases) (Faculty of Medicine Universitas Indonesia, 2006)
The objective of this study was to observe the results of adenomyosis mangement with resection and administration of aromatase inhibitor. Cases of ademyosis in infertile women were collected for three years (January 1999 to December 2001) and the diagnoses were confirmed using transvaginal USG. Cases were grouped into two groups, i.e. group 1 (undergoing laparotomic resection) and group 2 (receiving treatment with aromatase inhibitor of anastrozole). Both groups were evaluated for changes in clinical symptoms, rate of successful pregnancy, and postoperative recurrency rate. During three years as many as 1619 infertility cases were managed, and among which 66 (4.07%) cases of adenomyosis were diagnosed with transvaginal USG. As many as 55 cases were analyzed, i.e., 32 cases underwent resection and 23 cases received aromatase inhibitor. Of 32 cases of surgical resection, the histopathological results showed 30 (93.75%) cases of adenomyosis and 2 (6.25%) cases of uterus myoma. In the group undergoing resection three cases (9.4%) were successfully pregnant, i.e., two cases had live birth, one case ended up with 6-week abortion. Moreover, 25 (78.1%) cases were not pregnant and 4 (12.5%) cases had recurrency, while 24 (75.35%) cases experienced disappearance of symptoms yet not pregnant. On the other hand, of 23 cases in the group receiving aromatase inhibitor 2 (8.6%) cases were able to be pregnant, one case had live birth and another case ended up with abortion, while 14 (59.1%) cases had disappearance of symptoms yet not pregnant. During three months of treatment with aromatase inhibitor, a reduction in the lesion size between 7.31 mm3 and 25.90 mm3 were observed with CI 95% (p < 0.001). In conclusion, treatment with aromatase inihibitor did not heal lesions, but only reduced the size of adenomyosis lesions. On the other hand, resection could heal lesions, yet recurrency of disease may occur (12.5%) after one postoperative year. (Med J Indones 2006; 15:18-23) Keywords: adenomyosis, resection, aromatase inhibitor, anastrozole